Socialization Of Compliance In Taking Antihypertension Medication At Karang Anyer Community Health Center - Sitepu, Sari Desi Esta Ulina; Sipayung, Selamat Tuahta; Tarigan, Edi Kristianta (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Hypertension is a type of disease whose treatment requires patients to take medication for a long period of time, even for life. This disease can cause new diseases or various complications. So that this does not happen, a good level of compliance with the consumption of anti-hypertension drugs is needed in hypertension sufferers. By taking anti-hypertension medication you can stop the disease and normalize blood pressure levels. Compliance with treatment for hypertensive patients is the main key because hypertension is a disease that must be continuously controlled or managed so as not to cause complications with other diseases. This community service activity aims to socialize or educate the public about compliance with taking anti-hypertension drugs for hypertensive patients in the Karang Anyer Community Health Center working area. The method used was giving a pretest before the socialization was carried out and a posttest after the socialization was carried out on 25 people with hypertension who were participants in the socialization activities. From the results before the socialization was carried out, it was found that the majority of hypertension sufferers were not compliant in taking anti-hypertension medication namely 16 people (64%), and after carrying out socialization activities, it was found that there was an increase in the level of compliance of hypertension sufferers in consuming anti-hypertension drugs, namely 25 people (100%). Therefore, it can be concluded that this socialization or education activity can help hypertensive patients increase their compliance in taking anti-hypertension medication regularly.